Effect of alcoholic extract of tarantula cubensis (theranekron®) on serum thiobarbituric acid-reactive species concentrations in sheep - Burak Dik; Ayşe Er; Orhan Çorum (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the current research was to evaluate the effect of alcoholic extract of Tarantula cubensis on serum thiobarbituric acid-reactive species concentrations in sheep. Furthermore, it's effect on the hematological and biochemical values were determined. Materials and Methods: Six Akkaraman sheep were administered single dose (6 mL/sheep, SC) of alcoholic extract of Tarantula cubensis. Blood samples were obtained before (0 hour, control) and 2, 4, 8, 12, 24 and 48 hours after administration. Serum thiobarbituric acid-reactive species concentrations were measured by ELISA reader. The concentrations of biochemical and hemogram values were measured by autoanalyzer and blood cell counter, respectively. Results: Alcoholic extract of Tarantula cubensis dramatically decreased on serum thiobarbituric acid-reactive species concentrations in sheep but no statistically significant. In addition, it had no any negative effect on the hematological and biochemical values. Conclusions: It is stated that alcoholic extract of Tarantula cubensis may cause antioxidant effect and it may be accepted safe in sheep when evaluation of short time duration was considered.